Правове регулювання шлюбно-сімейних відносин у контексті становлення державно-правової системи України (XVIII-XX століття): історико-правове дослідження : автореф. дис. - Шевченко, Д. А.; Shevchenko, D. A. (Харків : Харківський національний університет внутрішніх справ, 2021)
Дисертаційну роботу присвячено дослідженню особливостей, закономірностей та правових засад регулювання шлюбно-сімейних відносин у контексті становлення державно-правової системи України у XVІII – XX столітті. Автором акцентовано увагу на тому, що актуальність проблем регулювання шлюбно-сімейних відносин і гострота питань, пов’язаних з ними, особливо помітні в нашій країні в умовах значних показників у депопуляції населення, а також, зростання кількості шлюборозлучних процесів, збільшення числа позашлюбних дітей та дітей-сиріт і позбавлених батьківського піклування. Ситуація, що склалася в сучасній Україні супроводжується посиленням нігілістичних тенденцій, які отримують своє вираження в криміналізації суспільних відносин, диференціації соціальної структури суспільства, посиленням конфліктності взаємин між представниками різних соціальних груп. Протидіяти подібним тенденціям можна за допомогою досить широкого спектру форм і методів впливу, в тому числі за допомогою зміцнення і стабілізації сімейних відносин. У сфері правового регулювання - це перш за все означає створення «якісного законодавства», яке було б направлене на дієве регулювання шлюбно-сімейні відносини, забезпечення реалізації прав і свобод за допомогою діючих юридичних гарантій, найважливіше місце серед яких відводиться державним гарантіям. У свою чергу, законотворча і правореалізаційна діяльність в даній соціально-юридичній сфері неможлива без достатньої ідейнотеоретичної бази, що включає аналіз досвіду, накопиченого як вітчизняною політико-правовою думкою, так і зарубіжним науковим надбанням та досвідом. Звісно ж, що осмислення генезису проблеми правового регулювання шлюбно-сімейних відносин і її ретроспективний аналіз дозволять не тільки виробити діючий механізм вирішення проблеми правового регулювання відносин у сфері сім’ї та шлюбу в сучасних умовах, а й застережуть від здійснення можливихпомилок, які мали місце в історичному минулому. У роботі на підставі вивчення наукової літератури, законодавчих та інших нормативно-правових актів, нормативних джерел, опрацювання архівних матеріалів здійснено системний історико-правовий аналіз правового регулювання шлюбно-сімейних відносин у контексті становлення державно-правової системи у XVІII – XX столітті та системно викладено інформацію про особливості реалізації окремих сімейних прав та обов’язків, а також інститут майнових прав подружжя. За результатами комплексного доктринального дослідження здійснено комплексне узагальнення широкого кола правових та наукових джерел, спеціальної наукової літератури, за результатами чого визначено закономірності становлення, розвитку правового регулювання шлюбно-сімейних відносин у XVIІI – XX століття.

The dissertation work is devoted to the study of the features, patterns and legal foundations of the regulation of marriage and family relations in the context of the formation of the state-legal system of Ukraine in the XVІII  XX centuries. The dissertation is devoted to the research of peculiarities, regularities and legal bases of regulation of marital and family relations in the context of formation of the state legal system of Ukraine in the XVIII  XX centuries. The author emphasizes that the urgency of the problems of regulation of marital and family relations and the severity of related issues are especially noticeable in our country in terms of significant indicators of depopulation, as well as the growing number of divorce proceedings, increasing the number of illegitimate children and orphans and children deprived of parental care. The current situation in modern Ukraine isaccompanied by the strengthening of nihilistic tendencies, which are expressed in the criminalization of social relations, differentiation of the social structure of society, increasing conflict of relations between representatives of different social groups. Such tendencies can be counteracted by means of a wide range of forms and methods of influence, including by means of strengthening and stabilization of family relations. In the field of legal regulation, this primarily means the creation of "quality legislation", which would be aimed at effective regulation of marital and family relations, ensuring the realization of rights and freedoms through existing legal guarantees, the most important of which is state guarantees. In turn, legislative and law enforcement activities in this socio-legal sphere are impossible without a sufficient ideological and theoretical basis, which includes analysis of experience gained by both domestic political and legal thought, and foreign scientific heritage and experience. Of course, understanding the genesis of the problem of legal regulation of marital and family relations and its retrospective analysis will not only develop an effective mechanism for solving the problem of legal regulation of relations in the field of family and marriage in modern conditions, but also warn against possible mistakes in the historical past. In the work on the basis of studying the scientific literature, legislative and other normative legal acts, normative sources, processing of archival materials the systematic historical and legal analysis of legal regulation of marital and family relations in the context of formation of the state legal system in XVIII  XX centuries is carried out. On the peculiarities of the implementation of certain family rights and responsibilities, as well as the institution of property rights of spouses. According to the results of a comprehensive doctrinal study, a comprehensive generalization of a wide range of legal and scientific sources , special scientific literature, which determined the patterns of formation, development of legal regulation of marital and family relations in the XVIII - XX centuries. The author determined that the urgency of the problems of regulating marriage and family relations and the acuteness of the issues associated with them are especially noticeable in our country in the context of significant indicators in population depopulation, as well as an increase in the number of divorce proceedings, an increase in the number of illegitimate children and orphans and deprived of parental custody. The situation that has developed in modern Ukraine is accompanied by an increase in nihilistic tendencies, which are expressed in the criminalization of social relations, the differentiation of the social structure of society, and an increase in the conflict of relations between representatives of various social groups. Such tendencies can be counteracted with the help of a fairly widerange of forms and methods of influence, including through strengthening and stabilizing family relations. In the field of legal regulation, this primarily means the creation of "quality legislation", which would be aimed at effective regulation of marriage and family relations, ensuring the exercise of rights and freedoms with the help of existing legal guarantees, the most important of which is given to state guarantees. In turn, lawmaking and law enforcement activity in this social and legal sphere is impossible without a sufficient ideological and theoretical base, including an analysis of the experience accumulated both by domestic political and legal thought and foreign scientific heritage and experience. Based on the results of a comprehensive doctrinal study, a comprehensive generalization of a wide range of legal and scientific sources , special scientific literature was carried out, according to the results of which the laws of the formation of the legal framework for regulating marriage and family relations in the context of the formation of the state legal system of Ukraine in the XVII-XX centuries were determined.

Диссертационная работа посвящена исследованию особенностей, закономерностей и правовых основ регулирования брачно-семейных отношений в контексте становления государственноправовой системы Украины в XVIII-XX веке. Автором акцентировано внимание на том, что актуальность проблем регулирования брачно-семейных отношений и острота вопросов, связанных с ними, особенно заметны в нашей стране в условиях значительных показателей в депопуляции населения, а также рост количества бракоразводных процессов, увеличение числа внебрачных детей и детей-сирот и лишенных родительской опеки. Ситуация, сложившаяся в современной Украине сопровождается усилением нигилистических тенденций, которые получают свое выражение в криминализации общественных отношений, дифференциациисоциальной структуры общества, усилением конфликтности отношений между представителями различных социальных групп. Противодействовать подобным тенденциям можно с помощью достаточно широкого спектра форм и методов воздействия, в том числе посредством укрепления и стабилизации семейных отношений. В сфере правового регулирования  это прежде всего означает создание «качественного законодательства», которое было бы направлено на эффективное регулирование брачно-семейные отношения, обеспечение реализации прав и свобод с помощью действующих юридических гарантий, важнейшее место среди которых отводится государственным гарантиям. В свою очередь, законотворческая и правореализационная деятельность в данной социально-юридической сфере невозможна без достаточной идейнотеоретической базы, включающей анализ опыта, накопленного как отечественной политико-правовой мыслью, так и зарубежным научным достоянием и опытом. Представляется, что осмысление генезиса проблемы правового регулирования брачно-семейных отношений и ее ретроспективный анализ позволят не только выработать действенный механизм решения проблемы правового регулирования отношений в сфере семьи и брака в современных условиях, но и предостерегут от осуществления возможных ошибок, которые имели место в историческом прошлом. Автором определено, что актуальность проблем регулирования брачно-семейных отношений и острота вопросов, связанных с ними, особенно заметны в нашей стране в условиях значительных показателей в депопуляции населения, а также роста количества бракоразводных процессов, увеличение числа внебрачных детей и детей-сирот и лишенных родительской опеки. Ситуация, сложившаяся в современной Украине сопровождается усилением нигилистических тенденций, которые получают свое выражение в криминализации общественных отношений, дифференциации социальной структуры общества, усилением конфликтности отношений между представителями различных социальных групп. Противодействовать подобным тенденциям можно с помощью достаточно широкого спектра форм и методов воздействия, в том числе посредством укрепления и стабилизации семейных отношений. В сфере правового регулирования  это прежде всего означает создание «качественного законодательства», которое было бы направлено на эффективное регулирование брачно-семейных отношений, обеспечение реализации прав и свобод с помощью действующих юридических гарантий, важнейшее место среди которых отводится государственным гарантиям.В работе на основе изучения научной литературы, законодательных и других нормативно-правовых актов, нормативных источников, обработки архивных материалов осуществлен системный историко-правовой анализ правового регулирования брачно-семейных отношений в контексте становления государственно-правовой системы в XVIII - XX веке и системно изложена информация об особенностях реализации отдельных семейных прав и обязанностей, а также институт имущественных прав супругов. По результатам комплексного доктринального исследования осуществлено комплексное обобщение широкого круга правовых и научных источников, специальной научной литературы, по результатам чего определены закономерности становления, развития правового регулирования брачно-семейных отношений в XVIII-XX века.
Автореферат дисертації на здобуття наукового ступеня доктора юридичних наук
Legal regulation of marital and family relations in the context of the formation of the state and legal system of Ukraine (XVIII-XX centuries): historical and legal research
Шевченко, Д. А. Правове регулювання шлюбно-сімейних відносин у контексті становлення державно-правової системи України (XVIII-XX століття): історико-правове дослідження : автореф. дис. ... д-ра юрид. наук : 12.00.01 / Д. А. Шевченко; МВС України, Харків. нац. ун-т внутр. справ. - Харків, 2021. - 50 с.
Keywords: Держава і право. State and Law. Государство и право; Цивільне право. Civil Law. Гражданское право; Історія. History. История; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.01; 081; Україна. Ukraine. Украина; шлюб; сім’я; шлюбно-сімейні відносини; сімейні правовідносини; подружжя; майнові права подружжя; немайнові права подружжя; майнові відносини подружжя; брак; семья; брачно-семейные отношения; семейные правоотношения; супруги; имущественные права супругов; неимущественные права супругов; имущественные отношения супругов; marriage; family; marital and family relations; family legal relations; spouses; property rights of spouses; non-property rights of spouses; property relations of spouses